1987
DOI: 10.1152/jappl.1987.62.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of granulocyte depletion in a ventilated surfactant-depleted lung

Abstract: In a previous paper Cutz, Bryan et al. showed that in rabbits after repetitive lung lavage high-frequency oscillatory ventilation maintained excellent gas exchange and did not cause hyaline membrane formation (J. Appl. Physiol. 55: 131-138, 1983). In contrast, conventional mechanical ventilation had poor gas exchange and extensive hyaline membrane formation and we attributed these differences to mechanical barotrauma. However, we completely overlooked the large number of granulocytes in the damaged lung. To in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0
10

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(140 citation statements)
references
References 0 publications
7
123
0
10
Order By: Relevance
“…More recently, experimental studies suggested that mechanical ventilation increases pulmonary levels of inflammatory mediators and induces neutrophil accumulation (14)(15)(16). These studies suggest the hypothesis that ventilator-induced lung injury has an inflammatory component.…”
Section: Introductionmentioning
confidence: 94%
“…More recently, experimental studies suggested that mechanical ventilation increases pulmonary levels of inflammatory mediators and induces neutrophil accumulation (14)(15)(16). These studies suggest the hypothesis that ventilator-induced lung injury has an inflammatory component.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, the use of isoflurane might have delayed the onset or reduced the magnitude of MV-elicited changes in inflammatory cell activation/migration in the lungs. Previous in vitro and in vivo studies demonstrated that mechanical deformation rapidly alter the phosphorylation of proteins in pulmonary parenchyma and immune cells, and that these changes could persist after MV was discontinued (37,38). In clinical settings, VILI can contribute to organ failure and increased mortality in patients with pre-existing lung disease (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…VILI'nın muhtemel mekanizmaları 9 hava boşluklarının tekrarlayan kollapsı ve yeniden açılması, 15 inflamasyon ve nötrofil artışı, 16 hemodinamik basınç değişiklikleri, 17 sür-faktan inaktivasyonu, akciğerde hücresel deformasyondur. 18 Şiddetli VILI'nın göstergelerinden biri alveoler ödemdir.…”
Section: Discussionunclassified